A COMPREHENSIVE REVIEW ON THE STRUCTURAL AND FUNCTIONAL MODULATION OF THE SKIN BARRIER: A HISTOLOGICAL AND IMMUNOHISTOCHEMICAL EVALUATION OF A MULTI-ACTIVE TEWL-REDUCING FORMULATION - Alyahya, Wasman Jaber (International Journal Multidisciplinary (IJMI), 2026)
Objective: This review aims to elucidate how a multi-active topical formulation can modulate skin barrier structure and function to reduce transepidermal water loss (TEWL), while positioning barrier biology as a translational framework for formulation science. Method: A comprehensive narrative synthesis of prior clinical, translational, and ex vivo studies was conducted, integrating histological and immunohistochemical (IHC) assessments of key barrier integrity markers—filaggrin, loricrin, involucrin, claudin-1, and ceramide-metabolizing enzymes—with functional measurements including TEWL, hydration, and electrical impedance. A conceptual three-phase model was developed, comprising an initial occlusive/humectant phase, a sub-acute differentiation and lipid restoration phase, and a long-term tight-junction recovery phase. Results: The analysis demonstrates a consistent theoretical correlation between changes in epidermal protein expression, lipid organization, and functional barrier outcomes, particularly TEWL reduction. Methodological considerations for histology and IHC evaluation, including sampling strategies, marker selection, and scoring approaches, are systematically discussed, alongside limitations of existing evidence. Novelty: This review offers an integrative molecular and functional framework that bridges formulation design and epidermal barrier biology, providing a translational model to guide future empirical validation and advanced topical therapeutic development.